2017
DOI: 10.1021/acs.jnatprod.6b01150
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Strebloside-Induced Cytotoxicity in Ovarian Cancer Cells Is Mediated through Cardiac Glycoside Signaling Networks

Abstract: (+)-Strebloside, a cardiac glycoside isolated from the stem bark of Streblus asper collected in Vietnam, has shown some potential for further investigation as an antineoplastic agent. A mechanistic study using an in vitro assay and molecular docking analysis, indicated that (+)-strebloside binds and inhibits Na+/K+-ATPase in a similar manner to digitoxin. Inhibition of growth of different high-grade serous ovarian cancer cells including OVCAR3, OVSAHO, Kuramochi, OVCAR4, OVCAR5, and OVCAR8 resulted from treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…Dg, deHyr, and Cy have also docked as Ob to the CG binding site in NKA with the same orientation of the steroid skeleton as Ob in the aforementioned NKA crystal structure [ 45 ]. The same orientation of the steroid skeleton was also observed in the crystal structure of NKA with digoxin [ 46 ] and strebloside, which is a structural analog of Cy [ 47 ]. However, deHyr and Cy showed higher binding energies compared to Ob caused by a lower number of interactions with NKA, which is due to the lower number of substituents on the steroid skeleton.…”
Section: Resultsmentioning
confidence: 53%
“…Dg, deHyr, and Cy have also docked as Ob to the CG binding site in NKA with the same orientation of the steroid skeleton as Ob in the aforementioned NKA crystal structure [ 45 ]. The same orientation of the steroid skeleton was also observed in the crystal structure of NKA with digoxin [ 46 ] and strebloside, which is a structural analog of Cy [ 47 ]. However, deHyr and Cy showed higher binding energies compared to Ob caused by a lower number of interactions with NKA, which is due to the lower number of substituents on the steroid skeleton.…”
Section: Resultsmentioning
confidence: 53%
“…The best small-molecule agents that can inhibit NKA activity are the cardiac glycosides that are composed of a sterol moiety linked to a glucoside 14,24 . Plumbagin and atovaquone do not share structural similarities with the known cardiac glycoside inhibitors of NKA [23][24][25][26][27] . Therefore, it is unlikely that plumbagin and atovaquone can serve as direct inhibitors of NKA.…”
Section: Discussionmentioning
confidence: 91%
“…Our results first demonstrated that digoxin treatment led to cell cycle arrest at the G0/G1 phase in SKOV-3 cells. It has been reported that CGs arrest the cell cycle in many cancers including glioblastoma, 35 breast, 22 ovarian, 28 and bladder cancers. 36 Digoxin treatment causes cell cycle arrest at the G0/G1 and G2/M phase for Raji and NAMALWA cells, and Burkitt’s lymphoma cell lines, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In ovarian cancer cells, it has been reported that bufalin and digitoxin arrest cell cycle at the G0/G1 and G2/M phases, respectively. 28 , 38 Recently, it has been shown that digoxin and digitoxin create anti-cancer effects on hepatocellular carcinoma by inhibiting the cell viability and migration. 39 It is apparent that not only reproduction-related cancers, but also the cancers of other systems are affected by digoxin and digitoxin.…”
Section: Discussionmentioning
confidence: 99%